The Struggle of Woman in Novel Merry Riana: Mimpi Sejuta Dolar by Alberthiene Endah: Existensialist Feminism Studies - Aji Septiaji; Yusi Nuraeni (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Literary work always presents variety of problem from the characters as roles in life that create the movement of a story, either male or female. This study focuses on the role of women who struggling to their lives so the readers can get different meanings and perspectives from female characters who are not victims of discrimination but as motivators to create their existence. The object of this research is a novel entitled Merry Riana: A Million Dollar Dream by Alberthiene Endah. This research employs qualitative method namely content analysis. The procedure in this research are intensive reading, identification, analysis, presentation, and conclusion. The focus of research on existentialist feminism are (1) women can work; (2) women can become intellectuals; (3) women can achieve socialist transformation; and (4) women can reject their motherhood nature. The result of this research is that the figure of a woman has the right to do or fight for something that is equal to men. The impact of the realization of ideals is to have a better life and give positive behavior. Keywords: woman, novel, existensialist feminism